2020
DOI: 10.1093/ajcn/nqz332
|View full text |Cite|
|
Sign up to set email alerts
|

Whey protein but not collagen peptides stimulate acute and longer-term muscle protein synthesis with and without resistance exercise in healthy older women: a randomized controlled trial

Abstract: Background Aging appears to attenuate the response of skeletal muscle protein synthesis (MPS) to anabolic stimuli such as protein ingestion (and the ensuing hyperaminoacidemia) and resistance exercise (RE). Objectives The purpose of this study was to determine the effects of protein quality on feeding- and feeding plus RE–induced increases of acute and longer-term MPS after ingestion of whey protein (WP) and collagen protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 46 publications
5
57
0
1
Order By: Relevance
“…Performance of RE serves to sensitize skeletal muscle to the anabolic effects of protein ingestion, such that rates of MPS are further enhanced when protein is consumed in temporal proximity to performance of RE [8,29]. Our finding that high repetition RE and supplementation with PP increased rates of MPS above the consumption of PP isolate alone is in line with previous acute measurements from our laboratory in healthy young men [8,29] as well as previous investigations measuring integrated rates of MPS in healthy older women [9,30,31]. Burd et al reported that both higher repetition (lower weight) and lower repetition (higher weight) RE when performed to volitional fatigue and combined with protein ingestion, facilitated elevations in MPS and the Akt/mTOR pathway for 24 h [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Performance of RE serves to sensitize skeletal muscle to the anabolic effects of protein ingestion, such that rates of MPS are further enhanced when protein is consumed in temporal proximity to performance of RE [8,29]. Our finding that high repetition RE and supplementation with PP increased rates of MPS above the consumption of PP isolate alone is in line with previous acute measurements from our laboratory in healthy young men [8,29] as well as previous investigations measuring integrated rates of MPS in healthy older women [9,30,31]. Burd et al reported that both higher repetition (lower weight) and lower repetition (higher weight) RE when performed to volitional fatigue and combined with protein ingestion, facilitated elevations in MPS and the Akt/mTOR pathway for 24 h [29].…”
Section: Discussionsupporting
confidence: 91%
“…The MPS response to amino acid feeding can vary markedly depending on the quality of the protein source. Specifically, complete proteins (a protein containing all of the essential amino acids [EAA]), and protein sources higher in leucine, augment rates of MPS to a greater extent than incomplete proteins and those lower in leucine [6][7][8][9][10]. Leucine is able to independently stimulate MPS through its interaction with mTORC1 [11], and thus, is critical for the determination of feeding-induced rates of MPS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the western population, there is an apparent shift towards increased consumption of plant-derived protein (in lieu of animal), due to perceived health benefits (e.g., reduced cardiovascular mortality [22]) and environmental sustainability [6]. Reflecting this shift, while the majority of prior research investigations have focused upon characterising the effects of animal-derived proteins in relation to musculoskeletal metabolism and health, there has been a recent surge of studies investigating the influence of plant-derived (e.g., References [4,[23][24][25]), collagen-derived (e.g., References [26][27][28][29]) and blended (e.g., References [30][31][32]) protein sources.…”
Section: Dietary Protein Requirementsmentioning
confidence: 99%
“…As such, collagen supplementation, in the form of collagen hydrolysates or gelatin, has recently gained popularity as an alternative or adjunct protein source to animal-and/or plant-derived sources for maintaining or even potentiating muscle and/or bone health (i.e., mass/function). This may seem counterintuitive since dietary collagen is rich in non-essential amino acids (NEAA's; e.g., proline, glycine), low in EAA's (e.g., methionine, leucine) and lacks tryptophan, rendering a DIAAS of 0 [27]. Expectedly, this has led to some questioning the anabolic potential of dietary collagen, at least compared to high-quality protein sources such as whey protein, which contain high levels of leucine and have a DIAAS of >1 [123].…”
Section: Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation